2010
DOI: 10.1371/journal.pgen.1001139
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Architecture of Complex Traits and Accuracy of Genomic Prediction: Coat Colour, Milk-Fat Percentage, and Type in Holstein Cattle as Contrasting Model Traits

Abstract: Prediction of genetic merit using dense SNP genotypes can be used for estimation of breeding values for selection of livestock, crops, and forage species; for prediction of disease risk; and for forensics. The accuracy of these genomic predictions depends in part on the genetic architecture of the trait, in particular number of loci affecting the trait and distribution of their effects. Here we investigate the difference among three traits in distribution of effects and the consequences for the accuracy of gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
336
0
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 362 publications
(370 citation statements)
references
References 37 publications
30
336
0
4
Order By: Relevance
“…This is potentially a common architecture for many complex traits (e.g. Hayes et al, 2010;Yang et al, 2010). The distribution of marker effects has implications for the findings of this genome-wide association study, and other QTL detection studies in the literature.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This is potentially a common architecture for many complex traits (e.g. Hayes et al, 2010;Yang et al, 2010). The distribution of marker effects has implications for the findings of this genome-wide association study, and other QTL detection studies in the literature.…”
Section: Discussionmentioning
confidence: 95%
“…However, the genetic architecture underlying such traits is poorly understood. Genetic architecture, that is, the size and distribution of polymorphisms affecting the trait, influences the success of association studies and the ability to predict future phenotypes, such as when predicting genetic risk to disease or when selecting livestock for breeding (Wray et al, 2007 ;Hayes et al, 2010). From an evolutionary perspective, knowledge of the genetic architecture in disease traits may help to elucidate the evolutionary influence of disease on hosts (Dawkins & Krebs, 1979).…”
Section: Introductionmentioning
confidence: 99%
“…For AGE26, the calibration dataset comprised those bulls born until December 2005 (n = 565) and the bulls in the validation dataset were born from January 2006 onwards (n = 550). Using birth date to define calibration and validation datasets is a tested approach (Hayes et al 2010). A GWAS for AGECL using the full dataset has been reported previously (Hawken et al 2012), but the results reserving 363 heifers for a validation exercise are reported only here.…”
Section: Genome-wide Association Studymentioning
confidence: 99%
“…Attempts to increase the power of association studies have focused either on increasing the number of markers or the number of observations for a trait. Few have attempted to formally estimate the distribution of marker effects with dense SNP markers (for example, Hayes et al, 2010;Kemper et al, 2011) and thus the required power of experiments for complex disease traits, such as nematode resistance, is still unknown. An alternate approach exploiting dense SNP chip data, known as Regional Genomic Relationship Mapping or Regional Heritability Mapping (RHM) (Nagamine et al, 2012), has been advanced as a better approach to capture more of the underlying genetic effects.…”
Section: Introductionmentioning
confidence: 99%